Insertion of principles of anthropogeomorphology on the secondary school: subsidies for the development of cartographic language and conceptions of physical geography - Pinton, Leandro de Godoi; Suizu, Tainá Medeiros; Matos, Augusto Luchesi; Oliveira, Lucas Celestino de (Geosaberes; Vol 10 No 22 (2019): Sept - Dec, 2019)
The objective of this work was to present the results of cartographic tests carried out by high school students to classify land use and land cover in a scenario possibly free from anthropogenic disturbance. Based on this presentation we aim to discuss the potential application of principles of Anthropogeomorphology for the development of skills related to the geographic reasoning of these students. The cartographic documents were elaborated based on photo interpretation of anaglyph images produced in a free software environment. The adaptation of methodological procedures of Anthropogeomorphology provided subsidies for the recognition of the stage of anthropic intervention in a past scenario, and also assisted in the preliminary analysis of the temporal evolution of land use and land cover and in the definition of violations of current environmental regulations. Thus, the theoretical and methodological assumptions adopted in this study constitute a resource in the teaching-learning process of cartographic language and environmental issues in secondary education.